A major histocompatibility complex class I–dependent subset of memory phenotype CD8(+) cells - Boyman, Onur (The Rockefeller University Press, 2006)
Most memory phenotype (MP) CD44(hi) CD8(+) cells are resting interleukin (IL)-15–dependent cells characterized by high expression of the IL-2/IL-15 receptor β (CD122). However, some MP CD8(+) cells have a CD122(lo) phenotype and are IL-15 independent. Here, evidence is presented that the CD122(lo) subset of MP CD8(+) cells is controlled largely by major histocompatibility complex (MHC) class I molecules. Many of these cells display surface markers typical of recently activated T cells (CD62L(lo), CD69(hi), CD43(hi), and CD127(lo)) and show a high rate of background proliferation. Cells with this phenotype are highly enriched in common γ chain–deficient mice and absent from MHC-I(−/−) mice. Unlike CD122(hi) CD8(+) cells, CD122(lo) MP CD8(+) cells survive poorly after transfer to MHC-I(−/−) hosts and cease to proliferate. Although distinctly different from typical antigen-specific memory cells, CD122(lo) MP CD8(+) cells closely resemble the antigen-dependent memory CD8(+) cells found in chronic viral infections.